Enabling reactive microscopy with MicroMator - Zachary R. Fox; Steven Fletcher; Achille Fraisse; Chetan Aditya; Sebastián Sosa-Carrillo; Julienne Petit; Sébastien Gilles; François Bertaux; Jakob Ruess; Gregory Batt (Nature Communications, 2022)
In microscopy, applications in which reactiveness is needed are multifarious. Here the authors report MicroMator, a Python software package for reactive experiments, which they use for applications requiring real-time tracking and light-targeting at the single-cell level.